Urban power load profiles under ageing transition integrated with future EVs charging - Haoran Zhang (Advances in Applied Energy, 2021)
Understanding ageing transition caused fine-grained changes of electricity profile is the significant insight for coping with future threatens in grid flexibility management. The research gaps for the hourly-basis knowledge exist due to challenges in microanalysis on user-side behavior. Based on billions of users’ behavior data, we investigated the changes on the load profiles due to population aging. We found that owing to ageing transition, the participation population in high electricity-density activities decreases by about 8%. The corresponding shift in driving behavior rises the 14% difference between peak charging load and valley. We concluded that population aging will dramatically change both the magnitude and shape of future dynamic-load profiles. Therefore, we further suggested a new solution with comprehensive and quantitative management for PVs development and the smart charging market with smooth operation of the grid in coupling the potential challenges caused by the ageing issue.